(untitled) (Orfeu, 2022)
Nowadays the historical process has suffered revisionisms in which remarkably personalities known as white persons or mulatto nicknamed, such as Machado de Assis, Mário de Andrade and Antônio Carlos Gomes, have been recognized from afrobrazilian origins. The pejorative terms were born with connotations derived from slavery, when the Brazilian State needed to elect whitened national symbols to exalt and become an industrialized pole in the tropics without the stigma that associated blackness to the discriminatory currents such as social Darwinism. One of these national symbols, in addition to the aforementioned ones, was Father José Maurício Nunes Garcia – whose Germanization went to history as the "Mozart fluminense" – born in Rio de Janeiro. By demystifying his whitening, the object of this study was to bring up elements that prove that he was really black, using anthropological methodology, in the same way that recent discussions show that the German composer Beethoven would have African ancestry.